1994
DOI: 10.1007/bf00772196
|View full text |Cite
|
Sign up to set email alerts
|

High-density culture of FM-3A cells using a bioreactor with an external tangential-flow filtration device

Abstract: A novel bioreactor system developed for high-density cultures of suspended mammalian cells is described using a tangential-flow filtration device outside the culture vessel to separate viable cells from spent medium. The filtration device is based on thin porous microfiltration membranes with a pore size of 0.20-0.65 microns. Because cells have a diameter of about 10-20 microns, they cannot permeate these membranes with the spent medium. So, allowing a perfusion culture to be created using this system. In most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In this system, the flow rate in the retention loop has to be optimized in order to minimize fouling and to avoid shearinduced disruption of the cells. Despite membrane rinsing or back-flushing, authors reported frequent fouling and clogging problems (de la Broise et al, 1991(de la Broise et al, , 1992Kawahara et al, 1994). Attempts to increase the efficiency of this technique were mainly conducted to increase membrane surface and tangential flow through module design, using channels in zigzag (de la Broise et al, 1991(de la Broise et al, , 1992 or spiral (Caron et al, 1994).…”
Section: Cross-flow Filtermentioning
confidence: 98%
See 1 more Smart Citation
“…In this system, the flow rate in the retention loop has to be optimized in order to minimize fouling and to avoid shearinduced disruption of the cells. Despite membrane rinsing or back-flushing, authors reported frequent fouling and clogging problems (de la Broise et al, 1991(de la Broise et al, , 1992Kawahara et al, 1994). Attempts to increase the efficiency of this technique were mainly conducted to increase membrane surface and tangential flow through module design, using channels in zigzag (de la Broise et al, 1991(de la Broise et al, , 1992 or spiral (Caron et al, 1994).…”
Section: Cross-flow Filtermentioning
confidence: 98%
“…This principle was tested by several investigators at small scale using specifically built modules with membranes in PVDF (Kawahara et al, 1994), Nucleopore (de la Broise et al, 1991Broise et al, , 1992, and polycarbonate (Caron et al, 1994). In this system, the flow rate in the retention loop has to be optimized in order to minimize fouling and to avoid shearinduced disruption of the cells.…”
Section: Cross-flow Filtermentioning
confidence: 99%
“…depth filter (de la Broise et al 1991;Velez et al 1989;Caron et al 1994;Kawahara et al 1994). The tangential movement reduces the filter fouling since the particles are not pressed into the filter membrane.…”
Section: Tangential Flow Filtration (Tff) and Alternating Tangential mentioning
confidence: 99%
“…Filtration-based techniques present problems of filter fouling after a relatively short period of operation (Kawahara et al 1994;Van Reis and Zydney 2001). Centrifuges may suffer from cell adhesion and clogging, besides their high mechanical complexity and high cost (Jäger 1992;Tokashiki et al 1990).…”
Section: Introductionmentioning
confidence: 99%